Association between the red blood cell distribution width–platelet ratio and the risk of in-hospital mortality in patients with alcoholic liver cirrhosis (with or without severe liver disease): a retrospective cohort study based on the MIMIC-IV database - Ning Liu; Bing Li; Junru Dai; Pengfei Shui; Bangbo Xia (BMJ Open, 2025)
Purpose The incidence of alcoholic liver cirrhosis (ALC) has been gradually rising in recent years, with a poor prognosis. This study aimed to investigate the association between the red blood cell distribution width–platelet ratio (RPR) and the in-hospital mortality risk among patients with ALC.Methods A total of 1424 patients with ALC were extracted from the Medical Information Mart for Intensive Care IV for carrying out this retrospective study. Based on the value of RPR, the included patients were divided into quartiles. The association between RPR and in-hospital mortality risk in patients with ALC, both with and without severe liver disease, was initially examined using Kaplan-Meier (KM) curves. Subsequently, restricted cubic splines (RCS) and multivariable Cox proportional hazards models were used to assess the relationship between RPR and in-hospital mortality. Subgroup analyses also explored the effect modifications by clinical covariates.Results Among the 1424 patients with ALC included, 778 were present with and 646 without severe liver disease. KM curves, RCS and multifactorial COX regression analyses suggested that patients in the first quartile (Q1) of RPR had the lowest in-hospital mortality risk, while those in the third quartile (Q3) had the highest. Among patients with total ALC, after the adjustment for all covariates, the HR for Q3 was 1.64 (95% CI 1.29 to 2.08, p<0.001); among those with severe liver disease, the HR for Q3 was 1.78 (95% CI 1.31 to 2.42, p<0.001); while among those without severe liver disease, the HR for Q3 was 1.27 (95% CI 0.89 to 1.83, p>0.05). Subgroup analysis revealed that factors such as age, blood pressure and medical history may affect the association between RPR and in-hospital mortality.Conclusion This study demonstrated a significant association between elevated RPR levels and increased in-hospital mortality risk in patients with ALC, including those with severe liver disease.